Framework de autenticação web via reconhecimento facial - Santos, Samuel F.; Tymburibá, Mateus (Companion Proceedings of the Brazilian Symposium on Cybersecurity (SBSeg); 2023: Companion Proceedings of the 23rd Brazilian Symposium on Information and Computational Systems SecurityDO - 10.5753/sbseg_estendido.2023.235089, 2023)
Authentication in web systems is an essential process to ensure the security and privacy of users. One way to enhance this process is to use facial recognition, which allows identifying users based on their facial features. In this article, we present a web application that uses facial recognition to enhance the authentication of users, using the FaceAPI from Microsoft Azure. The application was tested and analyzed under different aspects, such as the image format, the time interval and the facial recognition model. The results showed that the application is reliable and efficient. The application is also robust against changes in facial expressions and the use of facial masks.